2016
DOI: 10.1097/aud.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin Tone and Vowel Recognition in Cochlear Implant Users: Effects of Talker Variability and Bimodal Hearing

Abstract: Objectives For cochlear implant (CI) users with residual low-frequency acoustic hearing in the non-implanted ear, bimodal hearing combining the use of a CI and a contralateral hearing aid (HA) may provide more salient talker voice cues than CI alone to handle the variability of talker identity across trials. This study tested the effects of talker variability, bimodal hearing, and their interaction on response accuracy and time of CI users’ Mandarin tone, vowel, and syllable recognition (i.e., combined Mandari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…As can be observed in Figures 3 and 4, the results of tone, vowel, consonant and disyllable perception of the RW and cochleostomy groups were consistent with the previous studies [30][31][32], whereas the sentence perception of those patients was not good, which may be impacted by the different test material and approach. There was a significant difference between the 2 groups 3 months after implantation for the sentence perception, whereas there was no significant difference in tone, vowel, consonant, disyllable and sentence perception of the RW and cochleostomy groups 12 months after implantation.…”
Section: Discussionsupporting
confidence: 79%
“…As can be observed in Figures 3 and 4, the results of tone, vowel, consonant and disyllable perception of the RW and cochleostomy groups were consistent with the previous studies [30][31][32], whereas the sentence perception of those patients was not good, which may be impacted by the different test material and approach. There was a significant difference between the 2 groups 3 months after implantation for the sentence perception, whereas there was no significant difference in tone, vowel, consonant, disyllable and sentence perception of the RW and cochleostomy groups 12 months after implantation.…”
Section: Discussionsupporting
confidence: 79%
“…Many early studies assessed the perceptual effect of adding low-frequency acoustic information to electric hearing, and revealed the bimodal benefits in both non-tonal (e.g., Brown and Bacon, 2009;Carroll et al, 2011;Micheyl and Oxenham, 2012) and tonal (e.g., Luo and Fu, 2006;Li et al, 2014;Chang et al, 2016;Yang and Zeng, 2017) languages. As Mandarin Chinese differs with English in terms of the perceptual contribution of F0-contour or tonal information which is largely contained in the low-frequency region, the present work specifically examined the impact of preserving correct tonal information on bimodal benefits in Mandarin sentence perception.…”
Section: Discussionmentioning
confidence: 99%
“…They tested with the CI-only and CI þ HA conditions, and found combined-stimulation advantage for tone recognition in noise and vowel recognition in quiet, but not for consonant recognition. Chang et al (2016) found that in quiet, Chinese-speaking CI users' tone recognition significantly improved, but their vowel recognition did not significantly change with the use of a HA. The variable benefits of bimodal hearing to Mandarin speech recognition across studies might be due to the different degrees of residual acoustic hearing in individual subjects.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations